Synthesis and properties of tin dioxide nanostructures - Kufian, M. Z.; Mohamed Noor, Noraini; Osman, Z.; Z. Abidin, Z. H.; Arof, A. K. (Springer Nature, 2024)
Due to its high theoretical capacity of 1494 mAh g−1, tin dioxide, or SnO2, is a potential candidate for the anode in lithium-ion batteries (LIBs). SnO2 compounds can be derived from the mining sector, with Malaysia being one of the countries where tin is produced. However, utilizing SnO2 as an anode in LIBs has several disadvantages, including capacity loss brought due to the significant volume expansion of more than 300% that occurs during cycling and irreversibility of the conversion reaction, which reduces the anode’s initial coulombic efficiency (ICE). Several approaches have been used to address these issues, including reducing the size of the SnO2 particles to the nanoscale or producing a nanostructure, adding conductive carbon materials and using binders to increase the mechanical stability of the electrode. In this article, we focus on the process of creating nanoscale and nanostructure SnO2 and their properties to enhance battery performance.